(untitled) (The International Journal of Educational Sciences and Arts, 2023)
This reading undertakes the observation and analysis of fantasy manifestations in the play "From the Window" by Mulha Abdullah, representing a rich and renewed artistic experience in this field. It serves as fertile material for study and research, opening up historical dimensions, human legacies, and diverse cognitive discourses. The style reflects a conscious awareness that portrays reality and unreality as a vibrant material, embodying the external visualization of imaginary worlds, inner embedded feelings, desires, and dreams. The engagement of the audience, breaking expectations, and the use of unreality to expose thought and human phenomena are evident. The reading aims to examine this theatrical product, exploring language, description, character features, temporal and spatial formation, scenery, music, and costumes. It scrutinizes how these elements adhere to the creation of fantasy, regulating the fusion of the expected and unexpected through the dialectics of simplification, exaggeration, and blending reality with dream and symbol. This mechanism can converge with ancient narratives in creating an individual crisis and personal salvation, revealing influential ideologies on the writer and subsequently on the text. The study unveils the level of manifestation of implications and reservations, leading to perspectives on reception and the aesthetics of symbolic dimension in the text. The study demonstrates the effectiveness of thematic reading in the applied context on the written play. This research idea can contribute to applied studies on Saudi theatre.